Fairness of human resource management practices, leader-member exchange, and intention to quit / Mahfooz A. Ansari, Daisy Kee Mui Hung and Rehana Aafaqi - A. Ansari, Mahfooz; Hung, Daisy Kee Mui; Aafaqi, Rehana (Faculty of Business and Management ; UiTM Press, 2000)
We examined the impact of perceived fairness of human resource management (HRM) practices and quality of leader-member exchange (LMX) on the intention to quit the organization. In addition to the unique (negative) contribution of fairness of HRM practices and LMX, we hypothesized their interaction to predicting intention to quit. Two hundred twenty-four managers from nine diverse multinational, manufacturing companies in northern-Malaysia, voluntarily participated in the study. While certain interaction effects were significant, hypotheses for direct effects received substantial support. Key implications of the survey findings both for theory and for practice are discussed, and directions for future research are suggested.